Assessment of radar reflectivity-rainfall rate, Z-R relationships for a convective event in Malaysia - Sobli, Nuurul Hudaa; Ismail, Ahmad Fadzil; Mohd. Isa, Farah Nadia; Mansor, Hasmah (ETPub, 2013)
Abstract— Various relationships between radar reflectivity Z and rainfall rate R commonly identified as Z-R relationships have been derived in order to provide better accuracy for rainfall rate estimation using weather radar. It is critical for the air traffic management at the airport to accurately detect existence of potential microburst and wind shear. There are numerous factors that can certainly affect the accuracy of Z-R relationships including poor hardware calibration. However, the inaccuracy of Z-R relationships also might be due to the differences between the precipitation at the ground level and the precipitation aloft because radar does not scan all the way down except at close range. Several Z-R relationships had also been proposed in the attempt to achieve better accuracy for rainfall estimates by radar system in the tropical region. Nonetheless, the most accurate Z-R relationship for Malaysia weather radar is yet to be investigated and to be identified within the study period. This paper presents the preliminary analyses of previously proposed Z-R relationships for Malaysia weather using new radar data and ground rainfall rate. Comparisons were made between values obtained from the previously proposed relationships for radar and the ground truth measurements. It was identified that the previously proposed relationships estimations are significantly lower than the rain gauge data.